2005
DOI: 10.1038/ni1276
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of inflammation: the beginning programs the end

Abstract: Acute inflammation normally resolves by mechanisms that have remained somewhat elusive. Emerging evidence now suggests that an active, coordinated program of resolution initiates in the first few hours after an inflammatory response begins. After entering tissues, granulocytes promote the switch of arachidonic acid-derived prostaglandins and leukotrienes to lipoxins, which initiate the termination sequence. Neutrophil recruitment thus ceases and programmed death by apoptosis is engaged. These events coincide w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
1,805
1
34

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,144 publications
(1,929 citation statements)
references
References 72 publications
33
1,805
1
34
Order By: Relevance
“…This is in accordance with previous findings that androgens downregulate 5‐LOX product formation 9, 10, 37, 38. Most of these constitutive differences in oxylipid levels persisted after aspirin treatment and no sex‐specific effect of aspirin on oxylipid was observed, consistent with our previous findings in this population 4, 9, 11, 12, 39…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with previous findings that androgens downregulate 5‐LOX product formation 9, 10, 37, 38. Most of these constitutive differences in oxylipid levels persisted after aspirin treatment and no sex‐specific effect of aspirin on oxylipid was observed, consistent with our previous findings in this population 4, 9, 11, 12, 39…”
Section: Discussionsupporting
confidence: 93%
“…It is believed that reversal of inflammation is an active process that is as complex as the inflammatory response itself, and involves numerous pathways that are not all directly relevant to NF-kB (Serhan and Savill, 2005). Although the traditional view of NF-kB would lead one to imagine that it would primarily function by being turned off during the resolution phase of inflammation, recent work has suggested that NF-kB also has a more active role.…”
Section: Resolution Of Inflammation May Also Involve Nf-kbmentioning
confidence: 99%
“…However, a loss of regulation of these mechanisms can prevent the final resolution of the inflammatory process, leading to a chronic pathologic status. 1,2 Chronic inflammation is extremely relevant in today's modern medicine; it is now recognized that chronic inflammation contributes significantly to the pathogenesis of the most important diseases of industrialized societies, including atherosclerosis, cancer, and asthma. Given that chronic inflammation requires long-term pharmacologic treatments, new therapies with a lower degree of adverse effects are preferred.…”
mentioning
confidence: 99%
“…In the present study, we investigated the anti-inflammatory properties of AP214, an ␣-MSH analogue with the addition of a long N-terminal lysine sequence yielding high affinity for MC 1 and MC 3 over MC 5 . AP214 displays tissue-protective effects against renal postreperfusion injury, 19,20 but the mechanisms behind these tissue-protective actions have not been elucidated.…”
mentioning
confidence: 99%